THE CONCEPT OF JOINT VALUE CREATION AND TRANSFORMATION OF THE BUSINESS MODEL: PECULIAR PROPERTIES OF COMPANIES DIFFERENT IN THE TYPE OF PRODUCTION AND ECONOMIC INTERACTION - E. V. Migol (Финансы: теория и практика)
The article deals with the problem of transformation of business models of companies, which has become relevant for many of them in connection with the development of information technology and the emergence of real opportunities to include final consumers in the value chain. The features of this process for different types of companies are studied. The author analyzed 65 academic articles examining transformations of business models of particular companies. The analyzed companies were classified by two features: the type of economic interaction and the type of production. This makes possible to divide them into four groups. The author analyzes the problems, goals, and objectives of research for each of the four types of companies, as well as the scientific theories on which their authors rely.The purpose of the article is to identify the particularities of different types of companies, which are faced with the task of transforming business models, what, in turn, would allow companies to involve in the value chain of new members, more effectively create, deliver and withdraw value, as well as redistribute it among the rest of the participants.Content analysis is used to analyze academic articles published between 2010 and 2017, which are available in the databases of scientific citation Scopus and Web of Science. As a theoretical basis, we used service-dominant logic, Chesbrough and Rosenbloom’s concept of open innovation, Zott and Amit’s concept of action system and a number of others.The article concludes that Vargo and Lusch’s concept of service-dominant logic is the fundamental theoretical basis for most studies on business models and the theory of joint value creation. At the same time, depending on the type of company and the sector of the economy in which company acts, the practical problems faced by the company also vary, as well as the possible options for their solution. It is concluded that improving the business model of the organization, the researcher needs to take into account the business environment and the specifics of the sector.